Emperor and senators in the reign of Constantius II : maintaining imperial rule between Rome and Constantinople in the fourth century AD - Moser, Muriel (Cambridge classical studies, 2018)
In this book, Muriel Moser investigates the relationship between the emperors Constantine I and his son Constantius II (AD 312-361) and the senators of Constantinople and Rome. She examines and contextualizes the integration of the social elites of Rome and the Eastern provinces into the imperial system and demonstrates their increased importance for the maintenance of imperial rule in response to political fragility and fragmentation. An in-depth analysis of senatorial careers and imperial legislation is combined with a detailed assessment of the political context - shared rule, the suppression of usurpations, Constantius' use of Constantine's memory. Using a wide range of literary, epigraphic, numismatic, and legal sources, some of which are as yet unpublished, this volume produces significant new readings of the history of the senates in Rome and Constantinople, of the construction of imperial rule and of historical change in Late Antiquity.